Modern weapons and military equipment for issue 4-2024 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Russian new Iskander-1000 ballistic missile threatens Ukrainian F-16s and half of EuropeLockheed Martin Presents JASSM XR: An Extreme Range Cruise MissileDiscover Z-10ME: China's Attack Helicopter Presents for International Market at AAD 2024.